Media Literacy : Developing Critical Awareness Among Gen Z at SMA Sejahtera 1 Depok in Understanding the Genocide Tragedy in Gaza, Palestine - Andranurviza, Rachmayani; Rohmadtika Dita; Nyala Candrika Tifani (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2025)
The genocide in Gaza, Palestine, is often accompanied by propaganda that obscures the facts about human rights violations by Israel. This study aims to enhance Gen Z's media literacy so they can understand this tragedy from a moral perspective that upholds truth and justice. Through socialization activities, pre-test and post-test results show an improvement in students' understanding of the event. Additionally, this initiative encourages Gen Z to engage in humanitarian actions, such as fundraising and social activities, as a form of solidarity with the people of Gaza. Genosida di Gaza, Palestina, sering kali dipenuhi propaganda yang mengaburkan fakta pelanggaran hak asasi manusia oleh Israel. Penelitian ini bertujuan meningkatkan literasi media Gen Z agar mereka mampu memahami tragedi ini dengan perspektif moral yang berpihak pada kebenaran dan keadilan. Melalui kegiatan sosialisasi, hasil pre-test dan post-test menunjukkan peningkatan pemahaman siswa tentang peristiwa tersebut. Selain itu, kegiatan ini mendorong Gen Z untuk terlibat dalam aksi kemanusiaan, seperti penggalangan dana dan kegiatan sosial, sebagai bentuk solidaritas terhadap masyarakat Gaza.